PROYEK SISTEM INFORMASI PELAYANAN KESEHATAN BERBASIS WEB DI KLINIK INDOSEHAT 2003 WARAKAS - Abdussalaam, Falaah; Lariska, Novembri (INFOKOM (Informatika & Komputer), 2024)
Indosehat 2003 Warakas Clinic is one of the clinics located in Tanjung Priok, there areseveral obstacles and problems that occur at the Indosehat 2003 clinic, one of which isthat in providing health services, they still use a manual system where in making clinicreports they still use books so that they experience problems. Requires a long time inreporting, resulting in inconsistent patient data, double data, In order to meet thedemands and policies and laws and regulations from various parties such as the Ministryof Health and BPJS Health, the clinic is trying to develop technology. To support betterand more effective health services, it is necessary to improve by building a computerizedinformation system so that it can provide optimal service. The research method used isdescriptive method, with the system development life cycle (SDLC) approach method is amodel that proposes systematic and sequential software development to describe eachstage of the entire process. The SDLC model used is the waterfall model. The result ofthis project is an integrated health service information system that provides patientregistration information, examination results, drug prescriptions and payments, makingit easier in terms of reporting